Representations of Child Sexual Abuse in Jamaica A Corpus-Assisted Discourse Study of Popular News Media - Karpenko-Seccombe, Tatyana (MDPI Books, 2022)
News media shape public opinion on social issues such as child sexual abuse (CSA), using particular language to foreground, marginalize or legitimize certain viewpoints. Given the prevalence of CSA and the impact of violence against children in Jamaica, there is a need to examine the representation of children and their experience of violence in the news media, which remain the main source of information about such abuse for much of the population. The study aims to analyze accounts of CSA in Jamaican newspapers in order to show how different representations impact public understanding of CSA. This study offers a new perspective around child abuse by using an eight-million word corpus from articles over a three-year period (2018- 2020). The study argues that media reports often fail to conceptualise and represent accurately children who have experienced abuse. Representations of children are generic, their experiences often reduced to statistical summaries. Corpus analysis uncovered the use of terms which normalize sexual abuse. From the reader's perspective, there was little emotional connection to the child or the child's experience. The newspapers rarely report first-hand survivors' experience of abuse, depriving these children of a voice. Instead, a marked preference is given to institutional voices. An issue of concern is a tendency to sensationalism with disproportionate attention given to cases involving celebrities. By exposing these problems, the authors hope that news media in Jamaica can play a more positive role in heightening awareness around child abuse and allowing the voices of victims/ survivors to be heard.